The Model of Legal Protection for Children Victims of Domestic Violence Based on Justice - Andry Harijanto; Siti Hatikasari; Juliet Musabula (Journal of Human Rights, Culture and Legal System, 2022)
Indonesia has passed a policy on child protection and eliminating domestic violence. However, the critical question that needs to be asked is why violence against children increases yearly. This study aims to analyze the model of legal protection for children victims of domestic violence based on justice. This research is empirical research with primary, secondary, and tertiary data. This study concludes that the norms of Malay customary law that regulate violence in Bengkulu City, namely Cempalo Hand and Cempalo Mouth, can reduce violence against children in the household.